Social pressures and their relationship to the achievement motivation of handball players in Jordan - Jebril E Al-Awdat; Loay Mohammad Al-Shawabka; Randa Saleh Jawarneh; Mohammad Salim Al-Rawashdeh; Mohammad Ahmad Abu Haweeleh; Anan Hussein Bani Hani; Tamara Usama Farash (Universidad de Murcia, 2024)
This study aimed to assess the degree of social pressures and their relationship to sports achievement motivation among 51 randomly selected handball players from first-division clubs in Jordan. A descriptive approach was employed, and data were collected via a questionnaire, with analyses conducted using SPSS 26. The results showed that social pressure levels were moderate, with training pressures being the highest (M = 3.17; a relative importance of 63.40%), followed by family (M = 2.92; a relative importance of 58.40%) and public pressures (M = 2.32; a relative importance of 46.40%). No statistically significant differences were found in social pressures and sports achievement motivation among handball players based on experience (p > 0.05). While family and public pressures were not significantly correlated with motivation (p>0.05), training and overall pressures were positively correlated with motivation (p<0.05). The study found moderate social pressure among handball players in Jordan, with low public-related pressures and no differences based on experience. Motivation for sports achievement was high, with training-related pressures positively linked to motivation.